Processing Of Tin From Pegmatite - Parameswaran, Vengadesh (Universiti Sains Malaysia, 2018)
In this research, characterization and processing of tin have been done. The aim of this study is to identify the presence of tin and other heavy minerals in the granite pegmatite. Sample is dried and crushed using jaw crusher, cone crusher and ring mill which are there in the laboratory. Then, after sampling was done and four representative sample from the raw sample was taken and sent for XRF analysis to identify mineral compositions in the raw sample. Next, particle size distribution is done to see the characterization of minerals from four samples with different sizes. The samples are sent for XRF analysis to get the identification of minerals after processing. The optical microscope under polarized light is used to see the characterization of all the mineral in the sample. The concentrate sample is obtained after using Mozley table. The concentrate of the sample is then sent for analysis using XRD and XRF machine. The result from the XRD and XRF machines is analysed to identify the phases and mass percentage of tin oxide and other compound in the each sample. SEM machine is used to observe the heavy minerals based on the intensity of the mineral colour in the sample. Result shows that there are many heavy minerals in the sample when there is bright colour analysis is shown in the SEM result. XRD result shows the high content of silica. Hence, heavy minerals are hard to be determine. Analysis of the XRF result shows that there is tin present in the sample. Besides tin, there are some other heavy minerals too that are present such as ferrum oxide and aluminium oxide. Thus, the highest percentage of tin in the sample is about 3.572%. The concentration can be increase if more efficient process is used such as spriral concentrator. Based on the analysis, the tin is mineable if the concentration is increased up to 70%.